Gouvernorat Kafr esch-Scheich, Ägypten. Landschaftsarchäologie und regionale Siedlungsnetzwerke um den Fundplatz Tell el-Fara‘in im Nildelta und Untersuchungen am antiken Fundplatz Kom el-Gir. Die Arbeiten des Jahres 2018 und Frühjahres 2019 - Schiestl, Robert (e-Forschungsberichte des DAI, 2019)
The focus of the work in the northwestern Nile delta shifted from a regional perspective to the local. The investigations concentrated on a Hellenistic-Late Roman settlement, Kom el-Gir, located about 4 km northeast of Buto (Tell el-Fara’in). Following the reconstruction of the regional waterscape the site’s immediate link to the adjacent Nile branch was explored by auger core drilling combined with an electric resistivity survey. Clear evidence for fluvial activity was detected north and east of the settlement. A small scale test excavation on Kom el-Gir was able to confirm the existence of a Late Roman fort, as had been previously suggested based on magnetometric images. This provides the first archaeological evidence of a Roman fort from the interior of the Delta.